Immunoglobulins may Modulate the Formation of Triple Helix DNA in Pathophysiological States - Tyagi, Manoj G. (Recent Research in Science and Technology, 2011)
<span style="font-size: 10pt; font-family: ";Arial Narrow";,";sans-serif";; mso-fareast-font-family: 'Times New Roman'; mso-bidi-font-family: 'Times New Roman'; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;">The Runt domain proteins are comprised mostly of <span style="font-size: 10pt; font-family: Symbol; mso-fareast-font-family: 'Times New Roman'; mso-bidi-font-family: 'Times New Roman'; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA; mso-ascii-font-family: 'Arial Narrow'; mso-hansi-font-family: 'Arial Narrow'; mso-char-type: symbol; mso-symbol-font-family: Symbol;">b<span style="font-size: 10pt; font-family: ";Arial Narrow";,";sans-serif";; mso-fareast-font-family: 'Times New Roman'; mso-bidi-font-family: 'Times New Roman'; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;">-strands arranged in an antiparallel fashion to from a <span style="font-size: 10pt; font-family: Symbol; mso-fareast-font-family: 'Times New Roman'; mso-bidi-font-family: 'Times New Roman'; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA; mso-ascii-font-family: 'Arial Narrow'; mso-hansi-font-family: 'Arial Narrow'; mso-char-type: symbol; mso-symbol-font-family: Symbol;">b<span style="font-size: 10pt; font-family: ";Arial Narrow";,";sans-serif";; mso-fareast-font-family: 'Times New Roman'; mso-bidi-font-family: 'Times New Roman'; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;"> barrel with an s-type immunoglobulin fold. It is interesting to note that the same fold is used in the DNA binding domains of several transcription factors. A common feature is that DNA binding is mediated by loops that extend from one end of the Ig-motif. These proteins bind to different DNA sequences and specific recognition is accounted for by variations in the details of the molecular interactions between the loop regions and the DNA. This review suggests that immunoglobulin fold proteins may play a key role in modulation and formation of triple helix DNA structure with implications for patho-physiological states.